2022
DOI: 10.1001/jamaneurol.2022.3285
|View full text |Cite|
|
Sign up to set email alerts
|

Association Between Alberta Stroke Program Early Computed Tomography Score and Efficacy and Safety Outcomes With Endovascular Therapy in Patients With Stroke From Large-Vessel Occlusion

Abstract: ImportanceEndovascular therapy (EVT) has been found to reduce functional disability in patients with acute stroke due to large-vessel occlusion. However, the extent of the ischemic region, measured using Alberta Stroke Program Early Computed Tomography Scores, may limit the efficacy of EVT.ObjectiveTo compare the efficacy and safety of EVT according to ASPECTS 3 or less vs 4 to 5.Design, Setting, and ParticipantsThe Recovery by Endovascular Salvage for Cerebral Ultra-acute Embolism—Japan Large Ischemic Core Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…As the RESCUE-Japan LIMIT trial, SELECT 2 trial, and TENSION trial excluded patients with LVO with baseline ASPECTS of 0 to 2, the ANGEL-ASPECT trial was, to our knowledge, the first RCT to investigate the effect of EVT in patients with LVO with ASPECTS of 0 to 2. The findings of this secondary analysis are concordant with a subgroup analysis of the RESCUE-Japan LIMIT trial, which demonstrated that EVT was associated with improved 90-day functional outcomes in patients with LVO with baseline ASPECTS of 4 to 5 but not in those with ASPECTS of 3 or less . However, the SELECT2 subgroup analysis suggests that patients with large ischemic core volume, defined as 70 mL or greater, 100 mL or greater, and 150 mL or greater, still derived benefit with EVT compared with medical management …”
Section: Discussionsupporting
confidence: 79%
“…As the RESCUE-Japan LIMIT trial, SELECT 2 trial, and TENSION trial excluded patients with LVO with baseline ASPECTS of 0 to 2, the ANGEL-ASPECT trial was, to our knowledge, the first RCT to investigate the effect of EVT in patients with LVO with ASPECTS of 0 to 2. The findings of this secondary analysis are concordant with a subgroup analysis of the RESCUE-Japan LIMIT trial, which demonstrated that EVT was associated with improved 90-day functional outcomes in patients with LVO with baseline ASPECTS of 4 to 5 but not in those with ASPECTS of 3 or less . However, the SELECT2 subgroup analysis suggests that patients with large ischemic core volume, defined as 70 mL or greater, 100 mL or greater, and 150 mL or greater, still derived benefit with EVT compared with medical management …”
Section: Discussionsupporting
confidence: 79%
“…19 In fact, a secondary analysis of RESCUE-Japan LIMIT revealed that EVT was associated with a significantly higher incidence of any ICH within 48 hours in patients with lower ASPECTS. 21 HERMES also showed that the incidence of symptomatic ICH after recanalization was four times higher in low ASPECTS cases compared with the medical treatment group. 22 However, the association of time course and ICH after reperfusion in patients with a large ischemic core has not been widely examined.…”
Section: Discussionmentioning
confidence: 88%
“…The small sample size prevented analysis of each ASPECTS category, but we recently showed in another sub-analysis that EVT is associated with improved outcomes in ASPECTS 4 to 5 cases but not in those with ASPECTS ≤3. 21 The association of time course and ASPECTS ≤3 is a future issue for consideration. We also note that DWI-MRI was the predominant imaging modality used to evaluate ASPECTS, and DWI-ASPECTS may be approximately one point lower than CT-ASPECTS.…”
Section: Discussionmentioning
confidence: 99%
“…1-3 After reading the full texts of these 3 RCTs, one was excluded as it did not provide data for the subgroup of patients presenting with baseline ASPECTS scores between 0 and 2 (eFigure 1, links.lww.com/WNL/D124). 3,5 An attempt was made to collect aggregate data for patients with baseline ASPECTS scores between 0 and 2 from the RESCUE-Japan LIMIT and TESLA trials, which was not possible.…”
Section: Resultsmentioning
confidence: 99%
“…com/WNL/D124). 3,5 An attempt was made to collect aggregate data for patients with baseline ASPECTS scores between 0 and 2 from the RESCUE-Japan LIMIT and TESLA trials, which was not possible. Twenty of 352 (5.7%) and 62 of 456 (13.6%) total participants enrolled in SELECT2 and ANGEL-ASPECT, respectively, had baseline ASPECTS scores less than 3.…”
Section: Resultsmentioning
confidence: 99%